An acid-resistant scratch-resistant cold-laminating film and a preparation method thereof
Patent Information
- Application Number
- CN202611259395.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]随着户外广告应用场景的不断拓展,现有PVC冷裱膜的性能缺陷逐渐凸显,已难以满足复杂户外环境下的使用需求,具体存在以下不足:
(1)优异的抗酸腐蚀性能:本发明的抗酸耐刮硬化涂层采用氟碳改性丙烯酸树脂为主树脂,氟碳基团在涂层表面富集形成致密保护层,能有效阻隔酸性物质(如H2SO4、HNO3、HCl等)的侵蚀;
Smart Images

Figure CN122976148A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of cold lamination technology, and in particular to an acid-resistant and scratch-resistant cold lamination film and its preparation method. Background Technology
[0002] Cold lamination film is applied to printed images by hand or with a cold laminator to prevent scratches, contamination, or water damage, thus protecting the image. A typical PVC cold lamination film product usually consists of a PVC substrate layer, a pressure-sensitive adhesive layer, and release paper (or release film). Its preparation method generally involves coating the pressure-sensitive adhesive onto the release paper, drying it in an oven, and then laminating it onto the PVC substrate.
[0003] With the continuous expansion of outdoor advertising applications, the performance defects of existing PVC cold lamination film have gradually become apparent, making it difficult to meet the needs of use in complex outdoor environments. Specifically, the following shortcomings exist: Poor acid resistance: Conventional PVC cold lamination film is susceptible to acid rain and industrial exhaust gases (such as SO2 and NO) when used outdoors. x Acidic substances such as α and β can corrode the film surface, causing fogging, loss of gloss, and powdering, which seriously affects the clarity and aesthetics of the image. Insufficient scratch resistance: Existing PVC cold lamination film has low surface hardness (pencil hardness is usually ≤2H), making it easy to be scratched by sharp objects during transportation, installation and daily use, resulting in damage to the image, and the scratches are difficult to repair; Insufficient weather resistance: When conventional products are exposed to outdoor ultraviolet light for a long time, the PVC substrate is prone to yellowing and embrittlement, and the pressure-sensitive adhesive ages and fails, resulting in blistering and peeling of the film layer; Lamination bubble problem: During the lamination process, existing cold lamination films are prone to generating bubbles between the image and the film layer due to poor air release performance of the adhesive layer, which affects the visual effect. Summary of the Invention
[0004] To address at least one of the aforementioned technical problems, this application provides an acid-resistant and scratch-resistant cold lamination film and its preparation method.
[0005] In a first aspect, this application provides an acid-resistant and scratch-resistant cold lamination film, which comprises, from top to bottom, an acid-resistant and scratch-resistant hardening coating, a substrate layer, a venting pressure-sensitive adhesive layer, and a release paper; The acid-resistant and scratch-resistant hardening coating is formed by UV curing of a coating comprising the following components: fluorocarbon modified acrylic resin, nano silica sol, organosilicon modified polyurethane acrylate, photoinitiator, leveling agent and anti-yellowing agent. The venting type pressure-sensitive adhesive layer contains hollow structural units, which are one of micro hollow glass microspheres, expanded perlite microspheres, or polymer hollow microspheres.
[0006] Preferably, the acid-resistant and scratch-resistant hardening coating comprises the following components by weight: 40-55 parts of fluorocarbon modified acrylic resin; 15-25 parts of nano-silica sol; the solid content of the nano-silica sol is 30%; 10-18 parts of silicone-modified polyurethane acrylate Photoinitiator 1173, 2-4 parts; Photoinitiator TPOL 1-2 parts; Leveling agent 0.3-0.8 parts; Anti-yellowing agent 0.5-1.5 parts; 8-15 parts of butyl acetate; 5-10 parts of propylene glycol methyl ether acetate.
[0007] Preferably, the particle size of the nano-silica in the nano-silica sol is 10-30 nm; the dry film thickness of the acid-resistant and scratch-resistant hardening coating is 3-8 μm; and the surface contact angle of the acid-resistant and scratch-resistant hardening coating is ≥110°.
[0008] Preferably, the substrate layer is one of a PVC substrate layer, a PET substrate layer, or a PP substrate layer; When the substrate layer is a PVC substrate layer, the PVC substrate layer is a cross-linked PVC resin film with a thickness of 80-150μm, a light transmittance of ≥90%, and a haze of ≤7%.
[0009] Preferably, the hollow structural unit is a micro-hollow glass microsphere with a particle size of 20-50 μm, and the amount added is 2-5% of the solid content in the venting type pressure-sensitive adhesive layer.
[0010] Preferably, the venting type pressure-sensitive adhesive layer is one of solvent-based acrylic pressure-sensitive adhesive layer, water-based acrylic pressure-sensitive adhesive layer, or UV-curable pressure-sensitive adhesive. When the exhaust-type pressure-sensitive adhesive layer is a solvent-based acrylic pressure-sensitive adhesive layer, its thickness is 20-35μm; The venting-type pressure-sensitive adhesive layer has a 180° peel force of 3-6 N / inch, an initial tack of 8-12, and a holding power of ≥24h.
[0011] Preferably, the release paper is one of single-coated coated paper, double-coated coated paper, double-coated coated paper, or double-coated coated paper. When the release paper is a single-layer coated art paper, its basis weight is 80-120 g / m². 2 The release force is 10-30 g / inch.
[0012] Secondly, this application provides a method for preparing the acid-resistant and scratch-resistant cold-laminated film described in the first aspect of this application, the method comprising the following steps: S1. Preparation of acid-resistant and scratch-resistant hardening coating: Fluorocarbon modified acrylic resin, organosilicon modified polyurethane acrylate, butyl acetate and propylene glycol methyl ether acetate are added to a dispersion tank and stirred and mixed. Then, nano silica sol is added and dispersed. Then, photoinitiator, leveling agent and anti-yellowing agent are added and stirred and mixed. The mixture is filtered, allowed to stand to defoam, and set aside for later use. S2. Surface treatment of PVC substrate: The PVC film is subjected to corona treatment; S3. Coating and UV curing: The hardened coating prepared in step S1 is coated onto the surface of the corona-treated PVC film and cured by UV to form an acid-resistant and scratch-resistant hardened coating. S4. Preparation of venting type pressure-sensitive adhesive coating: Mix solvent-based acrylic pressure-sensitive adhesive, organic solvent and hollow microspheres, stir, let stand to defoam, and set aside; S5. Coating and bonding: The venting type pressure-sensitive adhesive coating prepared in step S4 is coated onto the release surface of the release paper. After drying, it is hot-pressed and bonded to the PVC substrate treated in step S3, and then rolled up.
[0013] Preferably, in step S3, the UV lamp power for UV curing is 80W / cm, the curing speed is 15-20m / min, and the curing is carried out under a nitrogen protective atmosphere; In step S5, the drying temperature is a gradient drying of 70-100℃, and the hot pressing temperature is 50℃ and the pressure is 0.3MPa.
[0014] Preferably, in step S1, the stirring speed is 800-1000 rpm, the dispersion speed after adding nano-silica sol is 1500 rpm, and the dispersion time is 30 minutes. In step S4, the hollow microspheres are micro hollow glass microspheres that have been surface-treated with silane coupling agent, and the mixing and stirring speed is 400 rpm and the stirring time is 20 minutes.
[0015] Compared with the prior art, this application includes, but is not limited to, the following advantages: (1) Excellent acid corrosion resistance: The acid-resistant and scratch-resistant hardening coating of the present invention uses fluorocarbon modified acrylic resin as the main resin. The fluorocarbon groups are enriched on the coating surface to form a dense protective layer, which can effectively block the corrosion of acidic substances (such as H2SO4, HNO3, HCl, etc.). (2) High surface hardness and scratch resistance: Through the synergistic effect of nano silica sol and organosilicon-modified polyurethane acrylate, surface hardness and scratch resistance can be effectively improved.
[0016] (3) Excellent weather resistance: Fluorocarbon resin has high CF bond energy and is not easily damaged by ultraviolet light. When combined with anti-yellowing agent, after QUV accelerated aging test, the yellowing index ΔYI≤5.0 and the light transmittance decreases by ≤5%, while conventional products have ΔYI≥8.0 and the light transmittance decreases by ≥15%.
[0017] (4) Excellent air-venting and bonding performance: The micro-hollow glass microspheres in the air-venting pressure-sensitive adhesive layer form a three-dimensional air-venting channel, which allows air to be quickly discharged during the bonding process. The bonding bubble rate is ≤1% (conventional products ≥15%), which greatly improves construction efficiency and image quality.
[0018] (5) High transparency and low haze: The thickness of the acid-resistant and scratch-resistant hardened coating is controlled at 3-8μm, and nano-sized silica (particle size 10-30nm) is selected, which is far below the wavelength of visible light and will not produce light scattering. The overall film material has a light transmittance of ≥90% and a haze of ≤7%, ensuring true color reproduction of the image. (6) Good flexibility: Despite the high hardness of the coating, the coating does not crack when bent at 180° due to the toughening effect of silicone-modified polyurethane acrylate, making it suitable for curved surface bonding. Attached Figure Description
[0019] Figure 1 This is a schematic diagram of a multi-layer structure according to one embodiment of this application; Among them, 10 is an acid-resistant and scratch-resistant hardened coating; 20 is a substrate layer; 30 is a venting pressure-sensitive adhesive layer; 40 is a release paper; 41 is a silicone oil layer; and 42 is a single-layer coated paper. Detailed Implementation
[0020] To make the objectives, features, and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention are described in detail below with reference to examples. Several embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided so that the disclosure of the present invention will be more thorough and complete: See also Figure 1 This application provides an acid-resistant and scratch-resistant cold lamination film, which includes, from top to bottom, an acid-resistant and scratch-resistant hardening coating, a substrate layer, a venting pressure-sensitive adhesive layer, and a release paper; Specifically, the acid-resistant and scratch-resistant hardened coating is formed by UV curing of a coating comprising the following components: fluorocarbon modified acrylic resin, nano silica sol, organosilicon modified polyurethane acrylate, photoinitiator, leveling agent, and anti-yellowing agent. The venting type pressure-sensitive adhesive layer contains hollow structural units, which are one of micro hollow glass microspheres, expanded perlite microspheres, or polymer hollow microspheres.
[0021] In this design, the outermost acid-resistant and scratch-resistant hardening coating uses fluorocarbon-modified acrylic resin as the main film-forming material, with a CF bond energy as high as 485 kJ / mol. After curing, the fluorocarbon groups migrate and accumulate on the coating surface, forming a dense hydrophobic and oleophobic protective layer that can effectively block acid rain, SO2, and NO. X To prevent penetration and erosion by acidic media, the coating surface is protected from deterioration such as fogging, loss of gloss, and chalking. Nano-silica sol constructs a nanoscale rigid framework within the coating, directly enhancing surface hardness and scratch resistance. Organosilicon-modified polyurethane acrylate, as a cross-linking toughening component, forms an interpenetrating cross-linked network with fluorocarbon resin and nano-silica, maintaining high hardness while improving coating flexibility and preventing brittle cracking and peeling of the hardened coating. Uniformly dispersed hollow microspheres in the venting pressure-sensitive adhesive layer create three-dimensional continuous microventing channels within the adhesive layer, allowing air to escape rapidly through the gaps between microspheres during cold lamination, significantly reducing air bubble residue. The substrate layer and release paper provide structural support and adhesive layer protection, respectively. This four-layer structure works synergistically to simultaneously improve multiple performance aspects, including acid corrosion resistance, scratch resistance, weather resistance, yellowing resistance, and easy venting during construction, while ensuring high light transmittance and low haze optical performance. This significantly extends the service life and appearance retention of outdoor inkjet prints.
[0022] Furthermore, photoinitiators are used for UV curing to achieve rapid cross-linking and film formation. Leveling agents improve the smoothness of the coating surface and enhance gloss uniformity; anti-yellowing agents inhibit yellowing caused by ultraviolet radiation.
[0023] In some embodiments, the acid-resistant and scratch-resistant hardening coating comprises the following components by weight: 40-55 parts of fluorocarbon modified acrylic resin; 15-25 parts of nano-silica sol; wherein the solid content of the nano-silica sol is 30%; 10-18 parts of silicone-modified polyurethane acrylate Photoinitiator 1173, 2-4 parts; Photoinitiator TPOL 1-2 parts; Leveling agent 0.3-0.8 parts; Anti-yellowing agent 0.5-1.5 parts; 8-15 parts of butyl acetate; 5-10 parts of propylene glycol methyl ether acetate; In this scheme, 40-55 parts of fluorocarbon-modified acrylic resin are used as the main resin, which can form a continuous and complete film-forming matrix, ensuring the coating's basic performance in terms of chemical corrosion resistance and weather resistance, while avoiding the decrease in coating adhesion and significant increase in cost caused by an excessive proportion of fluorocarbon resin; 15-25 parts of nano-silica sol with a solid content of 30%, which translates to 4.5-7.5 parts of effective components, can form a uniform rigid filling network in the coating, significantly improving surface hardness and scratch resistance. At the same time, because the amount of nanoparticles added is controllable, it will not cause significant light scattering, ensuring the coating's high light transmittance and low haze optical performance; 10-18 parts of silicone-modified polyurethane acrylate are used as a crosslinking toughening agent, which can form a stable interpenetrating network with the main resin, precisely balancing the coating's hardness and toughness, and preventing the coating from bending and cracking under high hardness. The dual-photoinitiator 1173, used in combination with TPOL, can absorb different wavelengths of ultraviolet light, improving the curing uniformity of both the surface and deep layers and ensuring consistent overall cross-linking of the coating. The trace addition of leveling agents and anti-yellowing agents improves the surface smoothness and gloss uniformity of the coating while inhibiting yellowing caused by UV aging. The mixed solvent system of butyl acetate and propylene glycol methyl ether acetate can adjust the evaporation rate and viscosity of the coating, adapting to various coating processes such as microgravure printing and preventing defects such as sagging and pinholes. This formulation range has been validated and can stably achieve the core indicators of a coating contact angle ≥110° and pencil hardness ≥2H, while also considering production feasibility and cost control.
[0024] Furthermore, the photoinitiator 1173 is Darocur 1173. The leveling agent can be a polyether-modified polysiloxane; the anti-yellowing agent can be a benzotriazole UV-531.
[0025] In some embodiments, the particle size of the nano-silica in the nano-silica sol is 10-30 nm; the dry film thickness of the acid-resistant and scratch-resistant hardened coating is 3-8 μm; and the surface contact angle of the acid-resistant and scratch-resistant hardened coating is ≥110°. In this solution, the particle size of nano-silica is controlled at 10-30nm, which is much smaller than the wavelength of visible light (400-760nm). When the nanoparticles are uniformly dispersed in the coating, they will not cause scattering and diffuse reflection of visible light, thus maximizing the coating's high light transmittance and low haze, and preventing the hardened coating from affecting the color reproduction and clarity of the printed image. If the particle size is too large, it will lead to increased haze and a blurry image; if the particle size is too small, it is prone to agglomeration, significantly increasing the difficulty of dispersion and limiting the hardness gain. The dry film thickness range of 3-8μm is precisely matched: when the thickness reaches 3μm or more, a continuous and complete dense protective layer can be formed, giving full play to the acid resistance and scratch resistance of fluorocarbon resin and nano-silica, and avoiding problems such as pinholes and discontinuous protection due to excessively thin coatings; controlling the thickness within 8μm can prevent the coating from being too hard and brittle, which would cause bending and cracking, while controlling the coating cost and avoiding excessive overall film thickness from affecting winding and construction. With a surface contact angle ≥110°, the coating exhibits excellent hydrophobic and oleophobic properties. When acidic droplets fall onto the film surface, they will roll off in a spherical shape, making it difficult for them to adhere and penetrate for a long time. This not only shortens the interaction time between the acidic medium and the film surface, improving the acid corrosion resistance, but also gives the coating a certain self-cleaning ability. When used outdoors, it can reduce the adhesion of dust and stains, maintaining the smoothness of the film surface and the visual effect of the image over a long period of time.
[0026] In some embodiments, the substrate layer is one of a PVC substrate layer, a PET substrate layer, or a PP substrate layer; When the substrate layer is a PVC substrate layer, the PVC substrate layer is a cross-linked PVC resin film with a thickness of 80-150μm, a light transmittance of ≥90%, and a haze of ≤7%. In this solution, the substrate layer offers three optional materials: PVC, PET, and PP, to suit different application needs. PVC substrates are moderately priced and flexible, making them the mainstream choice for conventional outdoor advertising cold lamination films. PET substrates offer superior temperature resistance and dimensional stability, making them suitable for high-temperature construction or scenarios requiring higher dimensional accuracy. PP substrates are more environmentally friendly, meeting the requirements for low VOCs and recyclability. For the most commonly used PVC substrate, a cross-linked PVC resin film is selected. Cross-linking monomer copolymerization reduces molecular chain migration, such as copolymerization with vinylidene chloride, significantly reducing the problem of plasticizer migration and precipitation to the surface. This avoids defects such as film stickiness, decreased coating adhesion, and image contamination after long-term use, while simultaneously improving the substrate's chemical corrosion resistance and dimensional stability, and reducing film expansion and contraction under outdoor temperature and humidity changes. A thickness range of 80-150μm balances the stiffness and flexibility of the film: adequate thickness ensures sufficient support, preventing wrinkles during construction and facilitating handling; controlled upper thickness prevents the film from being too rigid, ensuring proper adhesion when laminating curved surfaces. With optical parameters of ≥90% light transmittance and ≤7% haze, the substrate itself ensures that it will not negatively affect the color and brightness of the printed image. Combined with the low haze design of the hardened coating, the overall film material can truly reproduce the details and colors of the printed image, meeting the visual requirements of advertising displays.
[0027] In some embodiments, the hollow structural unit is a micro-hollow glass microsphere with a particle size of 20-50 μm, and the amount added is 2-5% of the solid content in the venting type pressure-sensitive adhesive layer; In this solution, the hollow structure unit offers three options: micro-hollow glass microspheres, expanded perlite microspheres, and polymer hollow microspheres, which can be adapted to different adhesive systems, cost, and performance requirements. Micro-hollow glass microspheres have high hardness, uniform size, stable air venting effect, and good weather resistance, making them the preferred choice for outdoor cold lamination films. Expanded perlite microspheres have lower cost and can be used for cost-sensitive low-end products. Polymer hollow microspheres have better flexibility, good compatibility with pressure-sensitive adhesives, and can be adapted to highly flexible adhesive layers. For micro-insulating glass beads, the particle size is controlled at 20-50μm to precisely match the thickness of the pressure-sensitive adhesive layer (20-35μm). The close proximity of the bead size to the adhesive layer thickness allows for the formation of uniform micro-protrusions on the adhesive surface, creating continuous three-dimensional venting channels. During lamination, air can quickly escape through the gaps between the beads. If the particle size is too small, effective protrusions cannot be formed, resulting in discontinuous venting channels and difficulty in resolving air bubble issues. If the particle size is too large, it will penetrate the adhesive layer, causing voids at the bonding surface, reducing peel strength, and even causing the beads to detach. An addition amount of 2-5% (relative to the solid content of the adhesive layer) has been validated for performance: at this addition amount, the beads can be uniformly dispersed in the adhesive layer, forming sufficient venting channels to ensure a lamination air bubble rate of ≤1%. Simultaneously, an excessively high proportion of beads does not lead to a significant decrease in the effective bonding area of the adhesive layer, avoiding substandard peel strength and holding power, thus achieving an optimal balance between venting and bonding performance.
[0028] Furthermore, the pressure-sensitive adhesive layer employs microsphere foaming and degassing technology, allowing air bubbles to escape along the gaps between the microspheres during lamination, thus preventing air bubble residue. Simultaneously, it is combined with solvent-based acrylic pressure-sensitive adhesive, exhibiting moderate initial tack and holding power.
[0029] In some embodiments, the venting type pressure-sensitive adhesive layer is one of solvent-based acrylic pressure-sensitive adhesive layer, water-based acrylic pressure-sensitive adhesive layer, or UV-curable pressure-sensitive adhesive; When the exhaust-type pressure-sensitive adhesive layer is a solvent-based acrylic pressure-sensitive adhesive layer, its thickness is 20-35μm; The 180° peel force of the venting type pressure-sensitive adhesive layer is 3-6 N / inch, the initial tack is 8-12 (ball number method), and the holding power is ≥24h; In this solution, the pressure-sensitive adhesive layer offers three optional adhesive systems: solvent-based, water-based, and UV-curable, to meet different environmental requirements and production processes. Solvent-based acrylic pressure-sensitive adhesives offer stable bonding performance and excellent weather and water resistance, making them the mainstream choice for outdoor cold lamination films. Water-based pressure-sensitive adhesives have low VOC content, meeting environmental production requirements and suitable for indoor applications or scenarios with stringent environmental standards. UV-curable pressure-sensitive adhesives offer fast curing speed, high production efficiency, and no solvent evaporation, making them suitable for high-speed coating production lines. For solvent-based acrylic pressure-sensitive adhesives, the adhesive layer thickness is set at 20-35μm. This thickness completely covers the hollow microspheres, preventing them from being exposed and affecting adhesion, while providing sufficient adhesive to ensure bonding strength. Furthermore, it avoids issues such as excess adhesive or edge sticking due to excessive thickness, and also controls adhesive layer costs. The combination of performance parameters—180° peel force 3-6 N / inch, initial tack 8-12, and holding power ≥24h—achieves a balance between ease of construction and long-term reliability: moderate initial tack ensures quick positioning during cold lamination, facilitating adjustments and preventing pasting errors; adequate holding power ensures the film layer will not peel or curl during long-term outdoor use, adapting to outdoor environmental conditions such as temperature differences and wind pressure; stable peel force ensures strong adhesion while also giving the cold lamination film a certain degree of repositionability, resulting in a higher tolerance for construction errors, and at the same time, it does not leave a large amount of adhesive residue on the surface of the image when removed, protecting the integrity of the mounted image.
[0030] In some embodiments, the release paper is one of single-coated coated paper, double-coated coated paper, double-coated coated paper, or double-coated coated paper. When the release paper is single-layer coated art paper, its basis weight is 80-120 g / m². 2 Release force is 10-30 g / inch; In this solution, release paper offers multiple options, including single-coated and double-coated coated paper, to suit different coating processes and adhesive systems. Single-coated coated paper offers moderate cost and good flatness, making it the mainstream release material for conventional solvent-based pressure-sensitive adhesives. Double-coated coated paper provides better solvent resistance and can be coated with silicone oil on both sides, adapting to more complex coating processes and winding requirements. For single-coated coated paper, the basis weight is controlled at 80-120 g / m². 2Release paper within this weight range possesses moderate stiffness and tensile strength, making it less prone to wrinkling and breakage during high-speed coating, drying, and lamination processes. This ensures uniform adhesive coating and improves production yield. Too low a weight results in a softer paper base, easily leading to coating breaks and uneven winding. Too high a weight increases product cost and overall weight, hindering transportation and use. The release force is controlled within the 10-30 g / inch range, having undergone dual verification in both construction experience and storage stability. A suitable release force ensures that the release paper and pressure-sensitive adhesive layer will not accidentally separate during storage and transportation, preventing adhesive contamination. Simultaneously, the release force is not excessive, allowing users to easily and smoothly remove the release paper without residual adhesive, film edge tearing, or displacement of the cold-laminated film during removal, thus ensuring both storage stability and ease of use.
[0031] This embodiment also provides a method for preparing the above-mentioned acid-resistant cold-laminated film, the method comprising the following steps: S1. Preparation of acid-resistant and scratch-resistant hardening coating: Fluorocarbon modified acrylic resin, organosilicon modified polyurethane acrylate, butyl acetate and propylene glycol methyl ether acetate are added to a dispersion tank and stirred and mixed. Then, nano silica sol is added and dispersed. Then, photoinitiator, leveling agent and anti-yellowing agent are added and stirred and mixed. The mixture is filtered, allowed to stand to defoam, and set aside for later use. S2. Surface treatment of PVC substrate: The PVC film is subjected to corona treatment; S3. Coating and UV curing: The hardened coating prepared in step S1 is coated onto the surface of the corona-treated PVC film and cured by UV to form an acid-resistant and scratch-resistant hardened coating. S4. Preparation of venting type pressure-sensitive adhesive coating: Mix solvent-based acrylic pressure-sensitive adhesive, organic solvent and hollow microspheres, stir, let stand to defoam, and set aside; S5. Coating and bonding: The venting type pressure-sensitive adhesive coating prepared in step S4 is coated onto the release surface of the release paper. After drying, it is hot-pressed and bonded to the PVC substrate treated in step S3, and then rolled up.
[0032] In this scheme, step S1 uses a step-by-step feeding method to prepare the hardened coating: first, the resin and solvent are mixed and dissolved, then nano-silica sol is added for dispersion, and finally, photoinitiator and additives are added and stirred. This feeding sequence avoids direct contact between nanoparticles and high-concentration resin, preventing agglomeration and ensuring uniform dispersion of nano-silica in the coating. Adding additives last reduces losses during dispersion and maintains their effectiveness. Filtration and defoaming processes remove impurities and bubbles from the coating, preventing defects such as particles and pinholes after coating. Step S2 involves corona treatment of the PVC substrate, which increases the surface energy of the substrate and enhances the interfacial bonding between the substrate and the hardened coating, preventing the coating from peeling off during use. Step S3 uses a UV curing process to form a film, which has a fast curing speed, high production efficiency, and controllable crosslinking degree, quickly forming a dense hardened coating. Low-temperature curing does not cause thermal deformation of the PVC substrate. Step S4 prepares a separate venting-type pressure-sensitive adhesive coating by mixing hollow microspheres with the pressure-sensitive adhesive and allowing it to stand for defoaming, ensuring uniform dispersion of the microspheres and preventing breakage. Step S5 employs a "release paper adhesive coating - drying - substrate hot pressing and bonding" process. First, pressure-sensitive adhesive is coated onto the release paper and the solvent is dried. Then, it is hot-pressed onto a substrate with a hardened coating. This process ensures uniform adhesive layer thickness and complete solvent evaporation, while hot pressing promotes wetting and bonding between the adhesive layer and the substrate, enhancing interlayer adhesion. The winding process ensures a flat finished product, facilitating subsequent slitting and storage. The overall process flow is coherent and rational, with controllable parameters for each step, enabling stable, large-scale production.
[0033] In some embodiments, in step S3, the UV lamp power for UV curing is 80W / cm, the curing speed is 15-20m / min, and the curing is carried out under a nitrogen protective atmosphere; In step S5, the drying temperature is a gradient drying of 70-100℃, and the hot pressing temperature is 50℃ and the pressure is 0.3MPa.
[0034] In this solution, during the UV curing process, an 80W / cm UV lamp power combined with a curing speed of 15-20m / min provides sufficient and suitable UV curing energy to the coating, ensuring that the fluorocarbon resin, polyurethane acrylate, and photoinitiator fully react to form a complete three-dimensional cross-linked network. Insufficient curing energy results in incomplete cross-linking of the coating, leading to a decrease in surface hardness, acid resistance, and weather resistance. Excessive energy, on the other hand, can cause over-cross-linking and embrittlement of the coating, and may even cause the PVC substrate to yellow and deform under heat. Using a nitrogen protective atmosphere for curing effectively isolates oxygen from the air, eliminating the inhibitory effect of oxygen polymerization on the surface curing of the coating, improving the curing degree and smoothness of the coating surface, reducing surface stickiness and insufficient hardness, and simultaneously reducing the risk of yellowing of the substrate and coating at high temperatures, thus improving weather resistance.
[0035] In the coating and bonding process, a gradient drying process of 70-100℃ is adopted. Through a temperature curve of gradual heating and cooling, the solvent in the pressure-sensitive adhesive evaporates slowly and evenly, avoiding rapid boiling of the solvent which could lead to pinholes and bubbles in the adhesive layer, thus ensuring a dense and uniform adhesive layer. Direct high-temperature drying can easily cause surface skinning and internal solvent residue, affecting adhesion performance and weather resistance. A hot-pressing temperature of 50℃ and a bonding pressure of 0.3MPa promote interfacial wetting between the pressure-sensitive adhesive and the PVC substrate, improving the bonding strength between the adhesive layer and the substrate. At the same time, this temperature and pressure will not cause thermal deformation of the PVC substrate or crush the hollow glass microspheres, ensuring the integrity of the venting structure and the stability of the adhesive layer performance.
[0036] In some embodiments, in step S1, the stirring speed is 800-1000 rpm, the dispersion speed after adding nano-silica sol is 1500 rpm, and the dispersion time is 30 minutes. In step S4, the hollow microspheres are micro hollow glass microspheres that have been surface-treated with silane coupling agent, and the mixing and stirring speed is 400 rpm and the stirring time is 20 minutes. In this scheme, in step S1 of preparing the hardened coating, the resin and solvent are first stirred and mixed at a speed of 800-1000 rpm. This speed ensures that the fluorocarbon modified acrylic resin and the organosilicon modified polyurethane acrylate are fully dissolved in the mixed solvent to form a uniform resin base liquid, while avoiding the introduction of a large number of air bubbles due to excessive speed. After adding the nano-silica sol, the speed is increased to 1500 rpm and dispersed for 30 minutes. The soft aggregates of nano-silica are broken by appropriate shear force, so that the nanoparticles are uniformly dispersed in the resin system, avoiding problems such as increased coating haze and uneven hardness distribution caused by local agglomeration. This combination of speed and time has been verified to achieve good dispersion effect without damaging the nanoparticle structure or causing resin degradation due to excessive shear.
[0037] In step S4 of the preparation of the venting-type pressure-sensitive adhesive, micro-hollow glass microspheres treated with a silane coupling agent are used. This introduces organic active groups onto the surface of the microspheres, significantly improving the interfacial compatibility between the microspheres and the acrylic pressure-sensitive adhesive, reducing microsphere sedimentation in the adhesive solution, and preventing the degradation of adhesive performance caused by interfacial voids, thereby improving the overall stability and durability of the adhesive layer. Using a low-speed stirring at 400 rpm for 20 minutes ensures uniform dispersion of the hollow microspheres in the adhesive solution while minimizing the damage to the hollow structure caused by stirring shear force, preventing the microspheres from breaking and losing their venting function. Excessive speed or prolonged stirring time can lead to the breakage of a large number of microspheres, preventing the formation of effective three-dimensional venting channels and directly affecting the lamination and venting effect. This process parameter effectively maintains the structural integrity of the microspheres and ensures stable venting performance.
[0038] The following specific embodiments will provide a more detailed description of the acid-resistant and scratch-resistant cold-laminated film of the present invention, but the present invention is not limited to the contents included in the embodiments. In the following embodiments, unless otherwise specified, substances with the same name represent the same type and quality of substance, and processes described in the same way represent the same process steps.
[0039] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0040] Examples 1-4 are listed below, all prepared by the following methods: (1) Under light-protected conditions, fluorocarbon modified acrylic resin, organosilicon modified polyurethane acrylate, butyl acetate, and propylene glycol methyl ether acetate were added to a dispersion vessel and stirred at 800-1000 rpm for 15 minutes; nano silica sol was slowly added and the speed was increased to 1500 rpm and dispersed for 30 minutes; photoinitiator, leveling agent, and anti-yellowing agent were added and the speed was reduced to 600 rpm and stirred for 10 minutes; the mixture was filtered (using a 200-mesh filter) and allowed to stand for 30 minutes to defoam before use.
[0041] (2) Select a 100μm thick high-transparency PVC film and treat it with corona (corona value ≥38 dyne) to improve surface adhesion. Apply the hardened coating prepared in step one to the corona-treated surface using a micro-gravure coating machine with a wet coating amount of 8-12g / ㎡. Cure it with a UV curing machine (UV lamp power 80W / cm, curing speed 15-20m / min, nitrogen protective atmosphere) to form an acid-resistant and scratch-resistant hardened coating with a dry film thickness of 5μm.
[0042] (3) Add solvent-based acrylate pressure-sensitive adhesive (solid content 45%), ethyl acetate, and micro hollow glass microspheres (particle size 30μm, surface treated with silane coupling agent) to a stirring vessel, stir at low speed of 400 rpm for 20 minutes to avoid breaking the microspheres, let stand for 15 minutes to defoam, and set aside.
[0043] (4) Using a coating and bonding equipment, the first unwinding is a single-coated copperplate release paper (silicone oil side up). The venting-type pressure-sensitive adhesive prepared in step four is applied to the silicone oil layer of the release paper using a comma-shaped doctor blade, with a wet adhesive amount of 50-70 g / m. 2 After drying in an oven (temperature settings: 70℃, 80℃, 90℃, 100℃, 100℃, 90℃, 80℃, 70℃), the adhesive layer thickness is 25μm. At the bonding station, the PVC substrate (primer side facing the adhesive layer) treated in step three is hot-pressed with the adhesive release paper (temperature 50℃, pressure 0.3MPa), and the finished product is then wound up.
[0044] (5) Cut the large roll of finished product into different widths (common widths: 0.914m, 1.07m, 1.27m, 1.52m) according to customer requirements using a slitting device, with a roll length of 30-50m, and inspect and package it.
[0045] The table below shows the different proportions of components in each of Examples 1-4. Table 1: Formulations of Acid-Resistant and Scratch-Resistant Hardening Coatings
[0046] Further: Example 1: Nano-silica particles with a diameter of 15 nm, dry film thickness of 5 μm, UV curing energy of 300 mJ / cm² 2 Suitable for general outdoor advertising.
[0047] Example 2: Nano-silica particles with a diameter of 20 nm, dry film thickness of 6 μm, UV curing energy of 350 mJ / cm² 2 Suitable for advertising in highly polluting industrial areas.
[0048] Example 3: Nano-silica particles with a diameter of 25 nm, dry film thickness of 4 μm, UV curing energy of 280 mJ / cm² 2 Suitable for displays requiring high light transmittance.
[0049] Example 4: Nano-silica particles with a diameter of 18 nm, dry film thickness of 7 μm, UV curing energy of 400 mJ / cm² 2 Suitable for applications requiring high scratch resistance.
[0050] Table 2: Formulation of Exhaust-Type Pressure-Sensitive Adhesive
[0051] Table 3: Comparative Example 1 Formulation (Fluorocarbon-free modification (retaining silicone-modified polyurethane acrylate)) Ordinary acrylic resin (fluorine-free modified) 48 copies Nano silica sol (30% solids content) 20 copies Organosilicon-modified polyurethane acrylate 14 copies Photoinitiator 1173 3 copies Photoinitiator TPOL 1.5 copies Leveling agent 0.5 copies Anti-yellowing agent UV-531 1 copy Butyl acetate 10 copies Propylene glycol methyl ether acetate 7 copies In this comparative example, the fluorocarbon-modified acrylic resin in Example 1 was replaced with ordinary acrylic resin (with similar molecular weight and solid content, but without fluorocarbon groups), while the remaining components and amounts were exactly the same as in Example 1, in order to separately verify the contribution of fluorocarbon modification to acid resistance and weather resistance.
[0052] Table 4: Comparative Example 2 Formulation (No Organosilicon Modification (Fluorocarbon Modification Retained)) Fluorocarbon modified acrylic resin 48 copies Nano silica sol (30% solids content) 20 copies Ordinary polyurethane acrylate (without silicone modification) 14 copies Photoinitiator 1173 3 copies Photoinitiator TPOL 1.5 copies Leveling agent 0.5 copies Anti-yellowing agent UV-531 1 copy Butyl acetate 10 copies Propylene glycol methyl ether acetate 7 copies In this comparative example, the silicone-modified polyurethane acrylate in Example 1 was replaced with ordinary polyurethane acrylate (with similar molecular weight and functionality, but without silicone segments). The remaining components and amounts were exactly the same as in Example 1, in order to separately verify the contribution of silicone modification to the coating hardness, scratch resistance and flexibility.
[0053] Table 5: Comparative Example 3 Formulation (without nano-silica (retaining fluorocarbon modification + organosilicon modification)) Fluorocarbon modified acrylic resin 58 copies Organosilicon-modified polyurethane acrylate 17 copies Photoinitiator 1173 3 copies Photoinitiator TPOL 1.5 copies Leveling agent 0.5 copies Anti-yellowing agent UV-531 1 copy Butyl acetate 12 copies Propylene glycol methyl ether acetate 8 copies In this comparative example, the nano-silica sol in Example 1 was removed, and the amounts of fluorocarbon modified acrylic resin and organosilicon modified polyurethane acrylate were increased accordingly to maintain a consistent total solid content. The remaining components and amounts were the same as in Example 1, in order to individually verify the contribution of nano-silica to surface hardness and scratch resistance.
[0054] Table 6: Performance Test Results
[0055] Test method description: 1. Acid resistance test: Cut the sample into 10cm×10cm pieces, drop 5% sulfuric acid solution on the surface, cover with a glass slide to prevent evaporation, clean and dry after 48 hours, and use a gloss meter to test the gloss retention rate.
[0056] 2. Surface hardness test: According to GB / T 6739-2006, use a pencil hardness tester to scratch the coating surface with a load of 750g at a 45° angle. The highest pencil hardness that does not scratch the coating is expressed as the highest pencil hardness.
[0057] 3. Scratch resistance test: Use steel wool #0000 with a load of 500g to rub back and forth on the coated surface 100 times, and visually evaluate the degree of scratches.
[0058] 4. Weathering resistance test: Tested using a QUV accelerated aging test chamber according to ASTM G154. 5. Transmittance / Haze Test: Test using a transmittance and haze meter according to GB / T 2410-2008.
[0059] 6. Bubble Rate Test: Laminate the cold lamination film onto a standard inkjet printing surface (image size 50cm×50cm), use a laminating machine at standard speed, and visually count the percentage of bubble area.
[0060] 7. Peel strength / initial tack / holding tack test: Performed according to GB / T 2792-2014 Test Method for Pressure Sensitive Adhesive Tapes.
[0061] Results analysis:
[0062] The above description is merely a preferred embodiment of this application and is not intended to limit this application in any way. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of this application shall fall within the scope of the technical solution of this application.
Claims
1. An acid-resistant and scratch-resistant cold laminating film, characterized in that: From top to bottom, it includes an acid-resistant and scratch-resistant hardening coating, a substrate layer, a venting pressure-sensitive adhesive layer, and a release paper; The acid-resistant and scratch-resistant hardening coating is formed by UV curing of a coating comprising the following components: fluorocarbon modified acrylic resin, nano silica sol, organosilicon modified polyurethane acrylate, photoinitiator, leveling agent and anti-yellowing agent. The venting type pressure-sensitive adhesive layer contains hollow structural units, which are one of micro hollow glass microspheres, expanded perlite microspheres, or polymer hollow microspheres.
2. The acid-resistant and scratch-resistant cold-laminated film according to claim 1, characterized in that: The acid-resistant and scratch-resistant hardening coating comprises the following components by weight: 40-55 parts of fluorocarbon modified acrylic resin; 15-25 parts of nano-silica sol; the solid content of the nano-silica sol is 30%; 10-18 parts of silicone-modified polyurethane acrylate Photoinitiator 1173, 2-4 parts; Photoinitiator TPOL 1-2 parts; Leveling agent 0.3-0.8 parts; Anti-yellowing agent 0.5-1.5 parts; 8-15 parts of butyl acetate; 5-10 parts of propylene glycol methyl ether acetate.
3. The acid-resistant and scratch-resistant cold-laminated film according to claim 1, characterized in that: The nano-silica sol has a particle size of 10-30 nm; the dry film thickness of the acid-resistant and scratch-resistant hardening coating is 3-8 μm; and the surface contact angle of the acid-resistant and scratch-resistant hardening coating is ≥110°.
4. The acid-resistant and scratch-resistant cold-laminated film according to claim 1, characterized in that: The substrate layer is one of PVC substrate layer, PET substrate layer or PP substrate layer; When the substrate layer is a PVC substrate layer, the PVC substrate layer is a cross-linked PVC resin film with a thickness of 80-150μm, a light transmittance of ≥90%, and a haze of ≤7%.
5. The acid-resistant and scratch-resistant cold-laminated film according to claim 1, characterized in that: The hollow structural unit is a micro hollow glass microsphere with a particle size of 20-50 μm, and the amount added is 2-5% of the solid content in the venting type pressure-sensitive adhesive layer.
6. The acid-resistant and scratch-resistant cold-laminated film according to claim 5, characterized in that: The venting type pressure-sensitive adhesive layer is one of solvent-based acrylic pressure-sensitive adhesive layer, water-based acrylic pressure-sensitive adhesive layer, or UV-curable pressure-sensitive adhesive. When the exhaust-type pressure-sensitive adhesive layer is a solvent-based acrylic pressure-sensitive adhesive layer, its thickness is 20-35μm; The venting-type pressure-sensitive adhesive layer has a 180° peel force of 3-6 N / inch, an initial tack of 8-12, and a holding power of ≥24h.
7. The acid-resistant and scratch-resistant cold-laminated film according to claim 1, characterized in that: The release paper is one of single-coated coated paper, double-coated coated paper, double-coated coated paper, or double-coated coated paper. When the release paper is a single-layer coated art paper, its basis weight is 80-120 g / m². 2 The release force is 10-30 g / inch.
8. A method for preparing an acid-resistant, scratch-resistant cold-laminated film as described in any one of claims 1-7, characterized in that: The preparation method includes the following steps: S1. Preparation of acid-resistant and scratch-resistant hardening coating: Fluorocarbon modified acrylic resin, organosilicon modified polyurethane acrylate, butyl acetate and propylene glycol methyl ether acetate are added to a dispersion tank and stirred and mixed. Then, nano silica sol is added and dispersed. Then, photoinitiator, leveling agent and anti-yellowing agent are added and stirred and mixed. The mixture is filtered, allowed to stand to defoam, and set aside for later use. S2. Surface treatment of PVC substrate: The PVC film is subjected to corona treatment; S3. Coating and UV curing: The hardened coating prepared in step S1 is coated onto the surface of the corona-treated PVC film and cured by UV to form an acid-resistant and scratch-resistant hardened coating. S4. Preparation of venting type pressure-sensitive adhesive coating: Mix solvent-based acrylic pressure-sensitive adhesive, organic solvent and hollow microspheres, stir, let stand to defoam, and set aside; S5. Coating and bonding: The venting type pressure-sensitive adhesive coating prepared in step S4 is coated onto the release surface of the release paper. After drying, it is hot-pressed and bonded to the PVC substrate treated in step S3, and then rolled up.
9. The preparation method according to claim 8, characterized in that: In step S3, the UV lamp power for UV curing is 80W / cm, the curing speed is 15-20m / min, and the process is carried out under a nitrogen protective atmosphere. In step S5, the drying temperature is a gradient drying of 70-100℃, and the hot pressing temperature is 50℃ and the pressure is 0.3MPa.
10. The preparation method according to claim 8, characterized in that: In step S1, the stirring speed is 800-1000 rpm, the dispersion speed after adding nano silica sol is 1500 rpm, and the dispersion time is 30 minutes. In step S4, the hollow microspheres are micro hollow glass microspheres that have been surface-treated with silane coupling agent, and the mixing and stirring speed is 400 rpm and the stirring time is 20 minutes.